2022
DOI: 10.1055/s-0042-1743239
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Education via WeChat Improves the Quality of Life of Parents of Children with Type-1 Diabetes Mellitus

Abstract: Objective The purpose of this study was to explore the effect of telehealth education and care guidance via WeChat (Tencent Ltd., Shenzhen, China; a popular smartphone-based social media application) on improving the quality of life of parents of children with type-1 diabetes mellitus. Methods A prospective randomized controlled study was conducted in our hospital from March 2019 to September 2020 to compare the quality of life of parents of children with type-1 diabetes mellitus in the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Diabetes related health was assessed in seven studies as glycemic control measured as Hemoglobin A1C (HgbA1C) levels. Two studies (29%) demonstrated a signi cant improvement in glycemic control in the mHealth group 51,52 ; in a third study (14%) the signi cant improvement favoured the control group. 37…”
Section: Diabetesmentioning
confidence: 96%
See 2 more Smart Citations
“…Diabetes related health was assessed in seven studies as glycemic control measured as Hemoglobin A1C (HgbA1C) levels. Two studies (29%) demonstrated a signi cant improvement in glycemic control in the mHealth group 51,52 ; in a third study (14%) the signi cant improvement favoured the control group. 37…”
Section: Diabetesmentioning
confidence: 96%
“…52,81,86 Resilience was signi cantly improved in two of the three (67%) studies which measured the construct 62,68 and quality of Life (QoL), which was assessed in seven studies, with scores signi cantly improved three (43%) of the times it was measured. 51,52,82 Social Psychological Outcomes A parent's relationship quality with their family, or their ill child, was measured in three studies. Two of the studies (67%) reported a signi cant improvement in the intervention group.…”
Section: Parent Psychological Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents had lower depressive symptoms at 9 months (postintervention) and 15 months (follow-up), with no impact on child glycemic outcomes; researchers noted the efficiency of stepped care in matching treatment intensity to family needs. A second RCT ( n = 92) investigated the impact of providing support via WeChat to newly diagnosed families in China [14 ▪ ]. Parents received health education modules via WeChat, and a medical staff member was available on WeChat for 3 h each evening to answer parent questions.…”
Section: Psychosocial and Behavioral Interventions For Children With ...mentioning
confidence: 99%
“…With respect to glycemia, nine studies reported favorable changes [12 ▪ ,13 ▪▪ ,14 ▪ ,15 ▪ ,22 ▪ ,23,26 ▪ ,28 ▪▪ ,30 ▪▪ ], seven found no change [9,10 ▪▪ ,16 ▪ ,18,19 ▪ ,21,31 ▪ ], and one reported an increase in HbA1c among intervention recipients [20 ▪ ]; five studies did not evaluate or report glucose metrics [8 ▪ ,24,25 ▪▪ ,27 ▪ ,29 ▪ ]. Psychosocial care is important independent of its relationship to glucose, and should be provided irrespective of the likelihood of improving glycemia.…”
Section: Overall Trends In Interventionsmentioning
confidence: 99%